THE RELATIONSHIP BETWEEN WOUND CARE TEQNIQUES AND THE LEVEL OF SATISFACTION OF DIABETES MELLITUS WOUND CARE PATIENTS - Anik Nuridayanti; Yusi Ari Kristanti; Sutik - (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
One of the potential causes of the increasing prevalence of diabetes mellitus is the occurrence of wounds. Uncontrolled wounds will get worse and hamper the healing process. The purpose of this study was to determine the relationship between wound care techniques and the level of satisfaction of diabetes mellitus wound patients This research design is analytic correlation with cross sectional design. The population in this study were all diabetes mellitus wound care patients as 30 patients, the sample was 30 respondents with total sampling technique. instrument in this study with a questionnaire. analyzed by the spearman rank test with α < 0.05.The results showed that most of the wound care techniques were good as many as 19 respondents (63.3%). Most of the patient satisfaction levels were good as many as 18 respondents (60%). From the results of the spearman rank test analysis, the p value = 0.000 < α = 0.05, the value of r = 0.932. There is a relationship between wound care techniques and the level of satisfaction of diabetes mellitus wound care patients. It is expected that wound care is carried out by competent nurses so that patient expectations can be realized and feel satisfied.